Sistem Informasi Manajemen Keuangan Usaha Mikro Berbasis Mobile - Nazar Wa’altaf; Muhammad Irwan Padli Nasution (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
This research discusses the development of a mobile-based micro-enterprise financial management information system as a solution to improve the efficiency and accuracy of financial management. Most micro-enterprises still use manual systems, resulting in slow and inaccurate recording and reporting processes. Through a mobile-based system, business owners can record and monitor their finances in real time using mobile devices. The system was developed using a cross-platform approach that supports various operating systems and is integrated through an Application Programming Interface (API). Security is enhanced by token authentication and data encryption. The analysis shows that implementing this system can accelerate financial processes, reduce recording errors, and increase transparency and management efficiency. Therefore, this system is an effective digital strategy for strengthening the competitiveness of micro-enterprises in the digital economy era.